In the shadow of Enoch Powell : Race, locality and resistance - Hirsch, Shirin (Book collections on Project MUSE., 2018)
Almost 50 years ago Enoch Powell made national headlines in what would become known as his 'Rivers of Blood' speech, warning of an immigrant invasion in the once respectable streets of Wolverhampton. This locale fixation brought the Black Country town into the national spotlight, yet Powell's unstable relationship with Wolverhampton has since been overlooked. Drawing from interviews and archival material, this book offers a rich local history through which to investigate the speech, bringing to life the racialised dynamics of space during a critical moment in British history. It traces the ways in which Powell's words reinvented the town, uncovering highly contested local responses. While Powell left Wolverhampton in 1974, the book returns to the area to explore the collective memories of Powell which continue to reverberate.